PENGARUH JENIS BAHAN PENGEMAS TERHADAP DAYA TAHAN CABAI MERAH (Capsicum annum L.) SELAMA PENYIMPANAN DINGIN - Fenny Agustina; Agam Akhmad Syaukani; Fatimah Sahara (SIMBIOSA, 2013)
The study was conducted over two months, from March to April 2012. This study aims to analyze the influence of type of packaging materials for durability of chilli (Capsicum annum L.) during cold storage. The method used in this study is an experimental method using a completely randomized design (CRD), which consists of four types of packaging materials, namely of chilli are packed in plastic PE, PP, PS, PS + control film with a red pepper that is stored without packaging. The parameters analyzed are severe shrinkage and the organoleptic (texture, color, aroma and overall). From the test results obtained ANAVA Fhitung value of 203,869 is greater than the value Ftabel, both at the level of 5% for 3,480 and 5,990 at 1% level. For the organoleptic value of PS + plastic film gives the highest yield in each test the texture attributes of 6,678. 6,500 color, aroma and overall 6,122 and 6,722. PP plastic gives the lowest result in each test the texture attributes of 3,156, 3,556 color, aroma and overall 3,333 and 3,300, this indicates that there is a very significant effect between the type of packaging materials for durability chili during cold storage.